Characterization of monocytic and granulocytic subsets of myeloid‐derived suppressor cells in blood donors with occult hepatitis B virus infection. Issue 2 (31st October 2018) - Zhang, Weiyun; Huang, Jieting; Wang, Min; Song, Dandan; Liao, Qiao; Rong, Xia; Li, Tingting; Allain, Jean‐Pierre; Ren, Guangli; Fu, Yongshui; Li, Chengyao
Abstract: Myeloid‐derived suppressor cells (MDSCs) accumulate from many diseases. MDSCs are rarely explored in occult hepatitis B virus infection (OBI). The frequency of monocytic MDSCs (M‐MDSCs) and granulocytic MDSCs (G‐MDSCs) in OBI carriers was analyzed for correlation with clinical parameters, which was no different between OBI and healthy individuals, whereas the frequency of M‐MDSCs but G‐MDSCs in OBI was significantly lower than that observed in chronic hepatitis B carriers (0.4% vs 0.7%, P  = 0.0004). The frequency of MDSCs was not correlated with clinical parameters and viral load of OBI, suggesting that the absence of HBsAg in OBI carriers might not induce the accumulation of MDSCs.